Optimizing expression of antiviral cyanovirin-N homology gene using response surface methodology and protein structure prediction - Lotfi, H.; Hejazi, M. A.; Heshmati, M. K.; Mohammadi, S. A.; Zarghami, N. (Cellular and Molecular Biology, 2017)
Cyanovirin-N (CVN) is well known as an anti-HIV protein. The efficient production of low cost microbicides for preventing the HIV-infection  has lately become a requirement worldwide. The aim of the present study was to optimize the expression of antiviral Cyanovirin-N homology gene found in the indigenous strain of Nostoc ellipsospourum LZN using Response Surface Methodology (RSM) and Protein Structure Analysis. Optimization of three induction factors (IPTG concentration (0.1, 0.55 and 1mM), temperature for bacterial growth (20, 28.5 and 37°C) and induction time (4, 10 and 16h) was done using RSM and Box-Behnken Design. Total RNA extraction was performed and mRNA levels were quantified in each experimental design by one-step SYBR qPCR. Protein structure was predicted using I-TASSER server. The full-length sequence of LZN-CVN gene is 306 bp in length, due mostly to five mutations. RSM analysis showed that the optimum condition to obtain maximum fold change was a concentration of 0.6mM IPTG, temperature set to 29°C and a 12h long induction time. The extracted protein from periplasmic fraction (8 kDa) was verified via SDS-PAGE. The high percentage of LZN-CVN similarity was demonstrated with PDB (Protein Data Bank) accession code of 2rp3A (CVN domain B mutant) and the ligand binding sites were related to N42, V43, D44, G45, S52, N53 and E56 residues. Different expression systems could assist in the development of anti-HIV proteins in a large scale. The LZN-CVN protein was successfully expressed in the E.coli system. RSM could be applied to a series of mathematical and statistical methods for modeling and analysis of responses which are influenced by various variables of interest.